Resistance to ceftriaxone and penicillin G among contemporary syphilis strains confirmed by natural in vitro mutagenesis - Petra Pospíšilová; Juraj Bosák; Matěj Hrala; Lenka Krbková; Eliška Vrbová; David Šmajs (Communications Medicine)
Abstract Background For many years, syphilis treatment was considered straightforward due to the universal susceptibility of Treponema pallidum subsp. pallidum (TPA) to penicillin antibiotics. Methods Penicillin-binding protein genes from a ceftriaxone treatment failure T. pallidum isolate were assessed, and the introduction of identified mutations into two laboratory strains via natural competence was aimed for, followed by in vitro analysis of antibiotic susceptibility of the recombinants. Results TPA from the ceftriaxone treatment failure case contained A1873G and G2122A mutations in the TP0705 gene. Introduction of the A1873G mutation into laboratory strains DAL-1 and SS14 resulted in partial resistance to ceftriaxone and penicillin G in vitro. Furthermore, in silico analyses revealed that the majority of contemporary TPA SS14-like strains harbors this mutation and are thus partially resistant to ceftriaxone and penicillin G. Conclusions This finding indicates that TPA strains accumulate mutations that increase their resistance to β-lactam antibiotics. Alternative approaches for controlling syphilis will be needed, including the development of the syphilis vaccine.